Teacher Education and Assessment based on a Proficiency Profile: A Proposal from a Reflective Practice Perspective - Arreola Rico, Roxana Lilian (2019)
The objective of this article is to provide a proposal for teacher education and assessment based on findings from a qualitative study that considers symbolic interaction and orality. An in-depth interview was used to recover oral narratives of students from a Mexico City high school. Results were analyzed according to a definition of empirical and analytical categories based on interviewee responses, which along with the theoretical categories, allowed us to better deconstruct, describe, understand and interpret classroom interaction. In other words, understand the students, teacher performance, educational practices and interact with social stakeholders within the school environment. Findings address student conceptions about teacher practices and characteristics that they consider necessary to be a good teacher. This study aims at formulating a system of guiding skills for teacher education and assessment as well as strategic actions for this system based on reflexive teaching practices focusing on teacher subjectivity.